Paraoxanase 1 Regulation of Cardiac Inflammation and Fibrosis in a Dahl Salt-Sensitive Rat Model of Chronic Kidney Disease - Sood, Ambika (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.